Scientific Explanation Skills in Dynamic Fluid through Problem-Based Learning Assisted by PhET Simulations - Nailunada, Novaliza; Yuliati, Lia; Wisodo, Hari (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to explore students' scientific explanation skills through the implementation of the Problem-Based Learning (PBL) model assisted by PhET simulations on the topic of dynamic fluids among high school students. The research employed a mixed-method approach with an explanatory model involving 58 eleventh-grade students. Data were collected through tests and interviews. Quantitative data were analyzed using a paired sample t-test, N-gain calculation, and effect size, while qualitative data were analyzed through data collection, reduction, coding, and drawing conclusions.The analysis results showed that the scientific explanation skills of students in the experimental class increased significantly compared to the control class. The paired sample t-test results indicated a significant difference between the experimental and control classes, and the N-gain score of 0.4096 indicated a moderate improvement. More students in the experimental class were categorized as fully supported, while the control class was dominated by students in the invalid category. The implementation of PBL assisted by PhET simulations proved effective in enhancing students' abilities to construct claims, provide evidence, and present logical scientific reasoning. In this study, the integration of PBL and interactive technology in science learning is suggested as a means to improve students' scientific explanation skills.